Conversational Implicature Through Maxim Flouting: A Pragmatic Analysis of Purple Hearts - Siti Amira Luthfiyah; Yanti Rosalinah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze the conversational implicatures in the movie Purple Hearts through maxim flouting. The study of implicature has become increasingly relevant in understanding how meaning is conveyed beyond literal expression, especially in audiovisual media where context and emotion play crucial roles. According to Grice’s (1975) Cooperative Principle, effective communication is achieved when participants adhere to four conversational maxims: quantity, quality, manner, and relation (relevance). However, implicature arises when these maxims are deliberately or unintentionally not observed. A descriptive qualitative method is used in this research to analyze conversational implicatures in selected dialogues from the film. This research specifically focuses on the phenomenon of flouting maxims. Based on the research, the flouting of the Maxim of Relation was the most frequent, appearing in 4 out of 10 cases (40%). This was followed by the Maxim of Quantity, Maxim of Quality, and Maxim of Manner, each occurring in 2 cases (20%). The findings are expected to contribute to a deeper understanding of pragmatic meaning and its implications for communication studies and film analysis.